The importance of Projovem Campo - Saberes da Terra in the Bico do Papagaio, Tocantins - Marcia Flausino Vieira Alves; Idemar Vizolli (Universidade Federal do Norte do Tocantins, 2022)
Education as a right for all permeates the paths of the contributions of Education in the Countryside. From this perspective, this study has as general objective to present the program ProJovem Campo Saberes da Terra and its importance for the formations of Young Family farmers in the Microregion of Bico do Papagaio, Tocantins. For this purpose, a qualitative approach was chosen for the generation and interpretation of data, in which bibliographic and documental consultation was used. From 2005 to 2012, ProJovem Campo - Saberes da Terra assisted 774 students at Bico do Papagaio, promoting social and professional training based on the Program's proposals. The data indicate the achievement of a Program that was developed for young family farmers, which, through the Family Agriculture and Sustainability course, promoted social and professional qualification with perspectives in contributing to the development of work, income generation and permanence of young people in their communities.